7 - Privatization and ‘Agentification’ of Public Services Delivery in Africa: Extent and Managerial Leadership Implications in Tanzania - Ngowi, Honest Prosper (Africa Development, 2021)
The paper dwells on the very current and topical issue of changing patterns and practices of public service delivery in Africa. The author offers a critical analysis and discussion on the extent to which public service delivery is being under- taken by the private sector (privatization) and executive agencies (‘agentification’) in Tanzania and the related managerial leadership implications. The article evi- dences the fact that over the last decade, Tanzania has taken many and far- reaching bold steps to reform its public sector and improve the performance of civil servants. Among the notable reforms is the participation of the private sector and executive agencies in the delivery of non-core public services through the private sector participation (PSP) initiative. The paper also shows that the privatization and ‘agentification’ of the public service delivery in Tanzania has a number of managerial leadership implications on the part of the public sector, the private sector and the executive agencies involved. Finally, the paper dem- onstrates that good managerial leadership, in the institutions involved in serv- ice delivery, is crucial if the objectives of privatization and ‘agentification’ of public service delivery are to be achieved.